The role of the hippocampus in the semantic variant of primary progressive aphasia: A resting‐state fcMRI study. Issue 11 (9th September 2019) - Chapleau, Marianne; Montembeault, Maxime; Boukadi, Mariem; Bedetti, Christophe; Laforce, Robert; Wilson, Maximiliano; Brambati, Simona M.
Abstract: The goal of the study was to determine whether the semantic variant of primary progressive aphasia (svPPA) affects the intrinsic connectivity network anchored to left and right anterior hippocampus, but spares the posterior hippocampus. A resting‐state functional connectivity MRI (rs‐fcMRI) study was conducted in a group of patients with svPPA and in controls, using a seed‐to‐voxel approach. In comparison to controls, massively reduced connectivity was found in the anterior hippocampus, mainly the left one, for svPPA patients but not in the left or right posterior hippocampus. In svPPA, the anterior hippocampus showed reduced functional connectivity with regions implicated in the semantic memory network. Significant correlation was also found between the functional connectivity strength of the left anterior hippocampus and the ventromedial cortex, and performance in semantic tasks. These findings indicate that the functional disconnection of the anterior hippocampus may be a promising in vivo biomarker of svPPA and illustrate the role of this hippocampal subregion in the semantic memory system.